Fundamentals of Investments - Cox Harold (American : Mc Graw Hill, 2008)
Fundamentals of Investment, Valuation and Management Canadian Edition was written to: 1. Focus on students as investment managers, giving them information they can act on instead of concentrating on theories and research without the proper context. 2. Offer strong, consistent pedagogy, including a balanced, unified treatment of the main types of financial investments as mirrored in the investment world. 3. Organize topics in a way that makes them easy to apply--whether to a portfolio simulation or to real life--and support these topics with hands-on activities. The approach of this text reflects two central ideas. First, there is a consistent focus on the student as an individual investor or investments manager. Second, a consistent, unified treatment of the four basic types of financial instruments--stocks, bonds, options, and futures--focusing on their characteristics and features, their risks and returns, and the markets in which they trade.
--This text refers to an alternate Hardcover edition.
Bradford D. Jordan is Professor of Finance and holder of the Richard W. and Janis H. Furst Endowed Chair in Finance at the University of Kentucky. He has a longstanding interest in both applied and theoretical issues in corporate finance and has extensive experience teaching all levels of corporate finance and financial management policy.
Keywords: Investments